Do indicators have politics? A review of the use of energy and carbon intensity indicators in public debates. (10th January 2020) - Rodriguez, Miguel; Pansera, Mario; Lorenzo, Pablo Cabanelas
Abstract: In this paper we analyse how energy and carbon intensity indicators, which have huge popularity among policy makers, are framed in the discourse of think tanks, consulting groups and other stakeholders. What emerges from the analysis of public documents, reports and policy briefs is that intensity indicators are often framed uncritically and unreflectively. Our analysis highlights three fundamental themes that emerge from public debates around intensity indicator. First, 'efficiency' and 'intensity' – often framed in terms of productivity – are used equivalently. Second, intensity is perceived as a measure of win-win sustainability in which economic growth can be decoupled from energy consumption without a substantial restructuring of the productive system. Third, the analysis suggests that energy and carbon intensity indicators are attractive for policy makers – especially in the so-called developing world – because they can be used to design political targets (e.g. Paris agreement) without questioning the right to economic growth of powerful emerging economies like the BRICS. The paper shows the strong limitations of intensity indicators and their potential do misguide policymakers.